Exchange Rate Policy in Developing Countries : Some Analytical Issues - Montiel, Peter (Occasional Papers; Occasional Paper ;, 1991)
This paper addresses analytical aspects of exchange rate policy and emphasizes the relationship among exchange rate flexibility, financial discipline, and international competitiveness.